An Analysis of Imperative Sentences of the Martian Movie and Their Subtitling - Muhammad Mahfudz Asrori; Hastuti Retno Kuspiyah; Ainur Rohmah (Channing : Journal of English Language Education and Literature, 2019)
This study concerns with the "An Analysis of Imperative Sentences of The Martian Movie And Their Subtitling". This study purposes problems are What the types of Imperative Sentence on the Martian Movie and their subtitling?. The main objective of this study is to know the imperative sentence of the martian movie and its subtitling. Therefore, this analysis used a descriptive qualitative method, documentation technique is used in collecting the data. By this method, the writer uses the subtitling of The Martian movie as the source of data. Based on the findings, the writer found that there are 2 types of imperative sentences, namely; (1) positive imperative sentence consisting of 70 data or 84.33%, and (2) negative imperative sentence consisting of 13 data or 15.67%. The most occurred was a positive imperative sentence consisting of 70 data or 84.33%.